Economic evaluation of the direct cost resulting from childhood poisoning in Morocco: micro-costing analysis - Fatima Zohra Benabdellah; Abdelmajid Soulaymani; Abdelrhani Mokhtari; Rachida Soulaymani-Bencheikh; Abderrazzak Khadmaoui; Hinde Hami (BMC, 2020)
Abstract Background The analysis of the economic burden for childhood poisoning has great value in Morocco where there still exists a paucity of information on the subject. The objective of this study was to explore the economic costs of unintentional and intentional poisoning in children in the region of Rabat-Salé-Kénitra, Morocco. Methods A prospective study of children younger than 15 years with a poisoning diagnosis conducted between March and July 2016 in the Children's University Hospital of Rabat, Morocco. The source of data for this study was questionnaire that collected information on the costs, the epidemiological and the socio-economic characteristics of childhood poisoning. Results Eighty-seven patients were interviewed during the study period (39 females and 48 males). The majority of poisoning cases (98.85%) were accidental and 1.15% were intentional. Drugs, snake bites and scorpion stings, carbon monoxide, food, plants, household products, illegal drugs, pesticides, petroleum and industrial chemicals products were caused the poisoning. Of all the hospitalized patients, 77 (88.5%) were admitted to the emergency department and 5 (5.7%) were admitted to the intensive care unit. The average direct medical costs and the average direct non-medical costs of providing poison treatment were USD 127 and USD 30 per child, respectively. Total average direct cost of USD 157 (127 + 30) represented 60% of the national minimum wage per month in Morocco. Total direct medical costs accounted for 80%, as against 20% direct non-medical costs. The mean ± SD length of stay (LOS) for children with poisoning was 2.15 ± 1.87 days with a range variated between 0 day and 10 days. Conclusions Overall, this study confirms that the costs of childhood poisoning are not negligible costs in Morocco. Therefore, the prevalence and the costs of childhood poisoning can be reduced by monitoring an open communication between parents, the Poison Control Centre of Morocco (MPCC) and physicians in order to increase the vigilance of parents against the risks related to unintentional poisoning that can be prevented with more awareness.